Influencia de las especies forestales Cordia alliodora “Laurel” y Calycophyllum spruceanum “Capirona” en el rendimiento de … - Hernandez Guevara, Eliecer (2014)
This thesis "Influence of Forest Species Cordia alliodora (Laurel) and Calycophyllum spruceanum (Capirona) performance of Theobroma cacao L in Agroforestry System Tocache, San Martín, 2013" aims to contribute to research regarding Systems agroforestry as a viable alternative, in order to improve production systems and yields per unit area. This way was chosen to perform this study on "Agroecology and Tourist Centre Eden" located in the province of Tocache, with a total area of 13 hectares in which different activities are being conducted tour and agroecological research nature. Thus in order to meet the objectives inventory to 100% of the two forest species described in this study in an area of l. 5 ha was made; area that is intended for the production of cocoa under this system, the methodologies followed are described in the literature cited; likewise for estimating the yield of "cacao" was chosen randomly 1.6% ofthe population of one hectare of cocoa the same as 1 collect the cobs are harvested according to plan Forester charge, proceeding and subsequent drying fermented drying of the samples to calculate their performance. The tree layer was evaluated with a total of 239 trees, ofwhich; Cordia alliodora species (Laurel) represents 76.6% of the stratum, with 183 trees assessed and a density of 1.22 trees /100m2 and species Calicophyllum spruceanum (Capirona) represents 23.4% ofthe stratum with 56 trees assessed and a density of 1.59 trees 1 300m2 ; in both species present over 90% straight stems; Scoring average height these trees are among the range of 18.3 to 21.6 meters with an average diameter of 21.6 cm and 23.8 cm respectively; Cordia alliodora species (Laurel) recorded a total return of 58.9 m3 1 ha and 44.5 m3 1 ha commercial volume and carbon sequestration estimated 17.3 tons 1 ha. the species Calicophyllum spruceanum (Capirona) recorded a total return of23.7 m3 1 ha and 16.6 m3 1 ha commercial volume and carbon sequestration estimated at 6.4 tons 1 ha. Finally the performance of "cacao" under this agroforestry system was estimated at 1.6 ton 1 year 1 ha.